Língua e cultura no ensino do ple/pls: reflexões e exemplos - Bizarro, Rosa (Linguarum Arena, 2018)
In this paper, we intend to reflect on two topics present in the process of teaching and learning a Foreign Language/Second Language, which are directly related to the role of an autonomous and critical citizen that the school (regardless the level of education) forms. We refer, in a concrete way, on one hand, the objects of teaching and learning and, secondly, intercultural mediation that should guide the actions of the teacher. We present, finally, some activities coming from the classroom of Portuguese as Foreign and Second Language that show how these theoretical principles can be implemented.